Revisiting volatility spillovers in the Gulf Cooperation Council - Salem Adel Ziadat; Ritab Al-Khouri (Cogent Economics & Finance, 2022)
This research offers a comprehensive review of the volatility spillover patterns in the Gulf Cooperation Council (GCC) stock market indexes covering daily data from 2/1/2004 to 5/11/2020. During this period, stock markets experienced fluctuations due to unexpected shocks, such as the international financial crisis, oil price shocks and, lately, the pandemic of COVID-19. The findings reveal a substantial increase in the connectedness of returns and volatilities in the GCC bloc during high stress periods with the COVID-19 era marking a historical high. That said, the results do not support significant changes in the directional patterns of volatility during the pandemic.
Keywords: 330; spillovers; correlation; international finance